THE USE OF ALTERNATIVE ASSESSMENT FOR UNDERGRADATE STUDENTS - Lailatul Fitriyah (Discovery : Jurnal Ilmu Pengetahuan, 2021)
Abstract In recent years, there are more choices to assess students’ abilities and understanding in language skill. As assessment plays an important role as the measurement in checking all steps and the results of language learning, this article describes a study that examine the use of alternative assessment for Indonesian undergraduate school students applied by English lectures from two different universities. This study uses surveys and interviews to examine (a) the process of alternative assessment for undergraduate students, (b) the students’ response using alternative assessment, (c) students’ result after being assessed by alternative assessment. So that, the conceptual frameworks taken from this study are: (a) alternative assessment’s process, (b) alternative assessment’s benefits, and (c) responsive pedagogy. This study also explores the impact of alternative assessment in assessing students in the classroom. The results of the survey revealed the majority of teachers felt that the alternative assessment helped them in assessing the students, as well as evaluating their beliefs and biases, thereby supporting the idea of incorporating more exercises and activities into English classes. The findings show that alternative assessment is necessary to be applied in teaching and learning since by applying this kind of assessment, the students be able to understand and can practice it in their daily activity. Alternative assessment also has positive response from students since it is understandable to be practiced.